PERJALANAN MENUJU PUNCAK AGRESI: STUDI FENOMENOLOGI-FORENSIK PADA REMAJA PELAKU PEMBUNUHAN - Masykur, Achmad Mujab; Subandi, Subandi (Faculty of Psychology, Diponegoro University, 2018)
Â Murder is essentially the culmination of an aggression which is still be a blind spot for the civilization of mankind. The incidence is quite high, but studies that specifically review it are still small. This research intends to deepen the crime of murder by focusing on causal factors, psychological dynamics and the impact of murder behavior on the perpetrators. Adolescents were chosen as subjects because murder cases conducted by teenagers also showed considerable numbers. The study was designed using a qualitative approach, a phenomenology of forensics which is a phenomenological approach that specifically reveals forensic cases related to murder offenses. Eight subjects participated in research conducted at the Kutoarjo Child Prison. Data in this study were collected through obeservation and interview with subject, psychological testing, home visit, and completed by an interview with prison officer and prison document data. The collected data interview is then analyzed using data explication method. This study finds that the dynamics of family factor interaction, social environment, friends, drug and alcohol abuse, socioeconomic status, education, individual psychological condition, availability of weapons, and the characteristics of the victim causing the killing behavior in adolescents. The impact of murder for the offender varies, depends on the background of the case.